Strategic management realignment in tandem with IR 4.0 / Baderisang Mohamed and Muna Abdul Jalil ... [et al.] - Mohamed, Baderisang; Abdul Jalil, Muna (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
IR4.0 or Industrial Revolution 4,0 refers to the current automation trend and data sharing practices in businesses. IR 4.0 is characterized by Internet of Things, Big Data and Analytics, Augmented Reality, Autonomous Robots, Additive Manufacturing, Cognitive Computing, and Cloud Computing (Vaidya, Ambad, & Bhosle, 2018). Strategic management processes involve strategy formulation, implementation, monitoring, and evaluating strategies to achieve company goals (Osborn, 2019). As IR4.0 revolutionizes the business industry, company strategic processes should be realigned with the wave of revolution. This paper determines whether strategic management processes should realign with IR4.0.